A study and practice of end-to-end quality of service analysis scheme for 5G services based on autonomous network - Shicheng XU (Dianxin kexue)
Conducting end-to-end analysis of 5G service quality is the focus of operators to improve 5G user perception.Technical solutions such as rule engine, AI competency center, and intelligent scheduling were adopted to build a “fifth order closed-loop autonomous process” covering quality difference identification, quality difference definition, closed-loop management, effect analysis, and model iteration related to 5G service quality analysis.The process can make up for the shortage of the traditional end-to-end analysis of service quality that highly relies on solidified expert rules.According to this process, the end-to-end analysis scheme of 5G service quality of self-intelligent network was studied and practiced, achieving efficient autonomous collaboration and ensuring the perception of 5G service users.